Strategic management paper for MAPFRE Asian Insurance Corporation - Dela Vega, Rolan L. (Animo Repository, 1998)
Mapfre Asian Insurance Corporation (MAIC) was incorporated on September 1, 1934 under the name Provident Insurance Company of the Philippines by the De Leon group of Companies. MAIC is one of the two composite insurance companies in the Philippines that are authorized to transact both life insurance business. In 1979, A. Soriano Corporation acquired 99.9% of its share, and it was renamed to Provident Insurance Corporation. In 1995, in line with the governments liberalization program, Corporation Mapfre of Madrid Spain acquired 59.9% of Anscor share, and it forged a joint venture with Asian Bank. The joint venture increased the combined paid-up capital to P300M. In January 1998, Sumitomo Fire and Marine acquired 6.67% of the companys share holding. This paper focuses on the LIFE AND NON-LIFE OPERATIONS of the company. The basic framework of Michael Porters internal strengths and weaknesses plus the external opportunities and threats and the five competitive forces were used as bases in the formulation of strategies. It contains five-year financial projections based on the recommended strategies and financial objectives of the company.